A preliminary global hydrochemical comparison of lakes and reservoirs - Dordoni, Marlene; Zappalà, Paolo; Barth, Johannes A. C. (Frontiers in Water, 2023)
Lakes and reservoirs are important for environmental anthropogenic functions in terms of agriculture and/or settlements. Here we present a first global overview of their chemistry by considering 1508 water bodies, with data from 485 peer-reviewed publications from 1868 to 2020 and further five online databases. This work focusses on major ions (Ca2+, Mg2+, Na+, K+, HCO3-&CO32-, Cl-, SO42-) and investigates analogies as well as differences between lakes and reservoirs. We applied a Principal Component Analysis (PCA) to group both types of water bodies and to find differences and similarities. The PCA identified fewer variabilities for major ions in reservoirs than in lakes. Moreover, our analyses showed that lakes generally have more total dissolved solids (TDS). Such higher TDS of lakes could result from more diverse (and less controlled) inputs from larger catchments and from longer lasting interactions with thicker internal sediment layers. Global median geochemical compositions identified both reservoirs and lakes as calcium-bicarbonate-type waters. This first synthesis provides a basis for future studies and may serve as the start of a global database on these important water bodies.